2008
DOI: 10.1007/s11109-008-9075-8
|View full text |Cite
|
Sign up to set email alerts
|

The Motivated Processing of Political Arguments

Abstract: We report the results of an experiment designed to replicate and extend recent findings on motivated political reasoning. In particular, we are interested in disconfirmation biases-the tendency to counter-argue or discount information with which one disagrees-in the processing of political arguments on policy issues. Our experiment examines 8 issues, including some of local relevance and some of national relevance, and manipulates the presentation format of the policy arguments. We find strong support for our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
260
4
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 374 publications
(293 citation statements)
references
References 17 publications
3
260
4
5
Order By: Relevance
“…Previous studies have identified motivating factors that generate more competent behavior and higher levels of knowledge (Luskin 1990;Eveland 2004). However, following the literature on motivated reasoning (Kunda 1990;Taber et al 2009), we argue that political attitudes motivate individuals to process information in a very different way, resulting instead in less competent behavior. People hold a variety of politically-related attitudes, some of them strong and stable, others are weak and variable.…”
Section: Responsibility Judgments Motivated By Political Attitudesmentioning
confidence: 92%
See 1 more Smart Citation
“…Previous studies have identified motivating factors that generate more competent behavior and higher levels of knowledge (Luskin 1990;Eveland 2004). However, following the literature on motivated reasoning (Kunda 1990;Taber et al 2009), we argue that political attitudes motivate individuals to process information in a very different way, resulting instead in less competent behavior. People hold a variety of politically-related attitudes, some of them strong and stable, others are weak and variable.…”
Section: Responsibility Judgments Motivated By Political Attitudesmentioning
confidence: 92%
“…Citizens with strong prior attitudes are often biased information processors, motivated by (dis)confirmation biases (Taber and Lodge 2006;Taber et al 2009). …”
Section: Responsibility Judgments Motivated By Political Attitudesmentioning
confidence: 99%
“…Attitude strength is the degree to which the attitude resists change, is stable, influences information and decision making processes, and predicts behavior (Krosnick & Petty, 1995). The relative strength or weakness of attitudes influences framing effects (Nelson, Clawson, & Oxley, 1997), survey response (Zaller, 1992), and polarization (Taber, Cann, & Kucsova, 2009;Wagner, 2007). To use the topic of this note as an example, strength of feelings regarding the job performance of President Barack Obama likely explains whether or not people remain silent or actively defend/attack him, whether they are ambivalent to his policy initiatives or eagerly embrace/reject them, whether attitudes toward Obama do or do not affect attitudes toward people perceived to be close to him (e.g., Joe Biden), and whether Obama-related political matters motivate people to vote and otherwise get involved in the political arena.…”
Section: Attitude Strengthmentioning
confidence: 99%
“…As a result, equally intelligent citizens may use the information that they have received through communication to support their own value predispositions, thus expanding ideological belief gaps (51,67,68). When individuals are motivated to discount messages that contradict their prior beliefs, they will invest effort into mentally denigrating and counterarguing this incongruent information, thereby reaffirming their current position, regardless of the message (69). In addition, values can bias assessments of the degree of scientific support for human causes of climate change; people overestimate the degree of certainty about and support for positions that are congruent with their value predispositions (50).…”
Section: Imcib In Context: Global Climate Changementioning
confidence: 99%